Intestinal Intramural Vascular Anastomoses. (2nd January 2016) - Cervellione, Raimondo M.; Varga, Gabriella; Hajnal, Daniel; Erces, Daniel; Kaszaki, Jozsef; Harwood, Rachel; Rakoczy, George; Cserni, Tamas
ABSTRACT: Introduction: Present surgical techniques are rarely relying on intestinal intramural vascular anastomoses; however, this could open new limits in reconstructive surgery. Our aim was to study the efficacy of the antimesenteric and the longitudinal intramural vascular anastomoses in a porcine model. Material and Methods: Five minipigs were used. Antimesenteric anastomoses: jejunal loops were detubularized by cutting along the antimesenteric line (Control), in the middle between the mesenteric and antimesenteric border (Group 1) and close to the mesenteric line (Group 2) . Mucosal microcirculation (red blood cell velocity, perfusion rate) was recorded with orthogonal polarization spectral imaging (Cytoscan A/R) at the long edge of the detubularized bowel. Longitudinal anastomoses: records were made on a continuous jejunal loop following antimesenteric incision, detubularization, and subsequent ligation of 2, 4, and 6 neighboring vasa recta in the middle of the loop. The same study was repeated on the free end of completely divided jejunal segments with ligation of 2, 4, or 6 vasa recta. Results: Antimesenteric anastomoses: There was no statistically significant difference in red blood cell velocity and perfusion rate between Control and Groups 1 and 2. Longitudinal anastomoses: The red blood cell velocity dropped significantly, while the perfusion rate did not change significantly after ligation of 4 vasa recta in the continuous loop. In the loop with a free end, however, both parameters decreased significantly after ligation of four vessels. Conclusion: It is safe to rely on antimesenteric intramural anastomoses but strong limitation of longitudinal intramural vascular anastomoses should be considered in intestinal reconstructions.